Synthesis, characterization and in vitro and in vivo anticancer activity of Pt(iv) derivatives of [Pt(1S, 2S-DACH)(5, 6-dimethyl-1, 10-phenanthroline)]. Issue 21 (17th May 2017) - Harper, Benjamin W. J.; Petruzzella, Emanuele; Sirota, Roman; Faccioli, Fernanda Fabiola; Aldrich-Wright, Janice R.; Gandin, Valentina; Gibson, Dan
Abstract : Synthesis and biological evaluation in vitro and in vivo of functionalized Pt(iv ) derivatives of Pt56MeSS. Abstract : This report describes the synthesis, characterization and biological activity of a series of platinum(iv ) derivatives of [Pt(1 S, 2 S -DACH)(5, 6-dimethyl-1, 10-phenanthroline)] (Pt56MeSS) with non-bioactive, lipophilic and bioactive axial ligands. In an attempt to explore the anticancer activity potential of the Pt(iv ) derivatives, 2D and 3D cytotoxic screening and a preliminary in vivo study were performed. The average IC50 values of the platinum(iv ) derivatives ranged from 1.26 to 5.39 μM, compared with 1.24 μM for Pt56MeSS, suggesting that the axial ligands have a relatively minor effect on the potency of the compounds. Preliminary in vivo studies indicate that the platinum(iv ) derivatives of Pt56MeSS are active in vivo and can reduce the tumor to a similar extent to cisplatin.